Inherent safety impact in complying process safety regulations and reducing human error - Rusli, R. (Elsevier, 2020)
The conventional practice of process safety management consists of the tremendous interdependency of the various elements such as identification of hazards, evaluation of risks and implementation of controls are heavily influenced by human factors. To ensure the success of process safety management for complex and dynamic environments where there are many variables and factors that can go wrong, a proper training program is needed for industry. While the training involving hard skills, such as equipment operation and understanding of regulations, can increase the safety level of a plant, major accidents have been recurring over the years (e.g., Flixborough accident, Bhopal accident, and Texas City accident). Other than human nature itself, a lack of focus on the key soft skills such as communication and crisis management that allow operators to respond effectively during incidents contributed to these accidents. The best way to resolve this issue is by proactively removing the source of the hazard itself through inherent safety implementation. This chapter will address the statistics on human error that lead to the accidents in chemical process safety, the basic inherent safety principles in process safety management, and how the implementation of inherent safety can reduce human error during operation. The benefits of inherent safety applications toward compliance of regulations, including evaluation of other type of control measures and training required to manage hazardous process will be demonstrated and discussed using case study. Â© 2021 Elsevier Inc. All rights reserved.